Appropriate geometrical ratio modeling of atrium for energy efficiency in office buildings - Nasrollahi, N.; Abdolahzadeh, S.; Litkohi, S. (Penerbit UKM, 2015)
Atrium refers to an open interior space that can be potentially related to an exterior environment. Indeed, atrium is considered as a filter and obstacle blocking undesirable exterior environmental phenomena such as rain, snow and wind. A well designed atrium can contribute to have a significant effect on both; the building's energy performance and indoor environmental conditions. In this paper, the aim is to study the effect of atrium ratio on energy efficiency and comfort of the occupants in an office building in the city of Tehran. In this work, the length to width ratio of the office buildings is identified and the average height of these buildings and validated appropriateness are examined by field studies. The simulation modellings of Design Builder Software is used to model various aspects of the building such as building materials, architecture construction, heating, cooling and lighting systems. One way ANOVA and Duncan’s multiple range tests are used to determine the differences of daylight and compare their averages in different models. It is shown that by decreasing the ratio of atrium to total building area from 1:2 to 1:10, the annual energy consumption reduces i.e., the highest and lowest annual consumed energy belong to the ratio of 1:2 and 1:10, respectively. Whereas from 1:2 to 1:10 ratio, regular downtrend has been occurred to received daylighting factors by the models. According to ANOVA performed on the intensity of daylight’s received height, significant differences were detected in different models with different atrium area ratios.Overall, the results show that ratio of atrium to total building area of 1:4 is the most efficient selection in terms of energy performance, daylighting and thermal comfort.